Spectral Triples in Particle Physics - Bochniak Arkadiusz (EPJ Web of Conferences, 2018)
We give an overview of the approach to the Standard Model of Particle Physics and its extensions based on the Noncommutative Geometry. The notion of spectral triples is introduced and their applications in particle physics are presented. We revisit known results based on different approaches within Noncommutative Geometry, list problems which appeared in these methods, propose possible solutions and indicate future directions of research.